Answer:
g(f(x)) = 1x² + 1
Step-by-step explanation:
We are given:
f(x) = x² - 1
g(x) = x + 2
And we want to find g(f(x)).
To do this, we substitute f(x) as x in x+2 (the expression that is equal to g(x)), as g(f(x)) is saying that f(x) is the value of x in g(x).
So, this will be:
g(f(x)) = x² - 1 + 2
Simplify
g(f(x)) = x² + 1
In your system, place 1 in front of x² - this is the coefficient of x², and also 1 after that - this is a constant.
Answer:
a>4
Step-by-step explanation:
-7a-11<1-4a
ADD 4a to both sides
-3a-11 <1
Add 11 to both sides
-3a <12
Divide both sides by 3
-a <4
Multiply by -1 both sides and FLIP SIGN
a>4
So a should be 5 ,6,7,8.........
On the number line you need to count from zero 4 units to the right (positive 4) Once you are in number 4 draw an open circle which means the 4 is NOT included) Draw a line from 4 to the right because it is bigger than 4.
Interval notation is (4,∞)
[ ] a square bracket when we want to include the number 4
( ) a round bracket when we don't want to include the number 4
<span>10x-5y=25 solve for y
so
10x - 5y = 25
5y = 10x - 25
y = 2x - 5
hope it helps</span>
Answer: 1) AC = 13
The formua does not actually apply to all of the problems.
Step-by-step explanation:
1) The absolute value of -8 is added to the absolute value of 5. 8+5=13
2) Subtract the length of the EF from EG to get the length of FG 21 -6 = 15
3) Take what's given and create an equation to solve. 4x + 15 +39 =110. 4x = 110 - (15+39).
4x =110-54. 4x =56. x=56/4. x=14
4) Create another equation. You have two segments that add up to the length of EG, given =23
EF+FG=EG
(2x-12)+(3x-15)=23
5x - 27 = 23
5x= 23+27 5x =50. x = 10
Substitute 10 for x
EF=2(10) -12 EF=8
FG=3(10)-15. FG=15
EF+FG =EG.
8 + 15 = 23
5) 2/5 of 25 is 10 So EF is 10. Subtract from 25 to get FG
FG = 15
I hope this helps you.